Experimental evaluation of retrofitting of partially damaged masonry houses using fiber reinforced coating - Kafle, Nitisha; Krishna, Chaitanya; Thanakorn Pheeraphan; Raktipong Sahamitmongkol; Computer and Structures Inc.(CSI), USA; AIT Scholarships (Pathum Thani, Thailand : Asian Institute of Technology, 2024)
This study proposes a potential solution to partially damaged unreinforced masonry buildings by fiber-reinforced paint. Static and dynamic tests were conducted, using a UTM machine and shake table, respectively, to assess the efficacy of the retrofitting technique. Results showed significant improvement in seismic capacity for retrofitted masonry, with enhanced performance in both in-plane and out-of-plane tests compared to unreinforced counterparts. Shake table tests on building models demonstrated the retrofitted structure's ability to withstand large deformations and dissipate energy effectively. Furthermore, ductility of the retrofitted structures was found to increase, indicating their ability to sustain large deformations without loss of structural integrity. Minimal dust emission during shaking table tests emphasized the safety aspect of the retrofitting method. Overall, the experiment concluded that fiber-reinforced paint is highly effective for enhancing the seismic resilience of partially damaged brick masonry. In this study, fiber-reinforced paint was the only retrofitting method considered for retrofitting.Thus, future investigations could involve combining localized failure repairs with fiber-reinforced paint to enhance its performance.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Structural Engineering
Thesis (M. Eng.) - Asian Institute of Technology, 2024
Keywords: Fiber-reinforced concrete -- Evaluation; Buildings -- Retrofitting; Earthquake resistant design